Symbols of Love and Sacrifice in the Poem Ishq az Awwal Chara Khuni Bud? by Jalaluddin Rumi: Semiotic Analysis of Ferdinand de Saussure - Ade Ahmad Suprianto (Raja Zulkarnain Education Foundation, 2026)
This study examines the symbols of love and sacrifice in the poem Ishq az Awwal Chara Khuni Bud? by Jalaluddin Rumi using Ferdinand de Saussure's semiotic theory. This poem presents the paradox of divine love, which is accompanied by suffering from the beginning, depicting humanity's spiritual journey toward union with God. The purpose of this study is to identify the linguistic signs (signifier and signified) that form the symbols of love and sacrifice, and to explain the meaningful relationships established through Rumi's poetic language structure. This study uses a qualitative descriptive method with a Saussurean semiotic approach, which emphasizes the analysis of the relationship between the signifier and the signified, as well as the paradigmatic and syntagmatic relationships between signs. Data were obtained through a literature review of the poem's text in the Masnavi-i Ma'navi anthology and supporting literature. The results of the study indicate that the words ishq (love) and khûn (blood) are central to the symbolic meaning that forms a spiritual sign system. Love is interpreted as a transcendental force that encourages union with God, while blood symbolizes suffering and self-purification (fana'). The relationship between the signs indicates that the meaning of divine love is constructed through the opposition between beauty and pain, as Saussure explained that meaning emerges through the differences between signs. Through this analysis, it is revealed that Rumi's linguistic structure functions not only as an aesthetic tool but also as a spiritual path to divine meaning. The symbol of love in this poem serves as a catalyst for spiritual awareness and a reflection on the human journey toward spiritual perfection. This finding strengthens the relevance of Saussure's semiotic theory in uncovering the Sufi dimensions of Islamic literary works.